Stacked light emitting device

By using organic electron transport materials and doped materials in composite materials, the problem of insufficient charge generation and separation capabilities of solution-based charge generation layers in stacked light-emitting devices was solved, thereby improving the charge transport and separation efficiency of the devices and enhancing device performance.

CN122318533APending Publication Date: 2026-06-30GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967768.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2026-06-30

AI Technical Summary

Technical Problem

Existing solution-based charge generation layers have poor charge generation and separation capabilities and conductivity in multilayer light-emitting devices, resulting in poor performance. Furthermore, inorganic N-type materials and organic functional materials cannot be effectively matched.

Method used

Composite materials, including combinations of organic electron transport materials (such as indene derivatives, fluorene derivatives, and indofluorene derivatives) and dopants, are used to prepare n-type layers. Solution processing is employed to reduce the possibility of leakage and improve charge generation and separation capabilities.

Benefits of technology

The performance of light-emitting devices has been improved by using the conjugate planar framework and coulombic bonding pairs of organic electron transport materials and doped materials to enhance charge transport and separation efficiency and reduce the risk of thin film cracking and leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122318533A_ABST
    Figure CN122318533A_ABST
Patent Text Reader

Abstract

This application belongs to the field of display technology and relates to a composite material, a composite film, and their applications. The composite material comprises an organic electron transport material and a doping material, wherein the organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo-fluorene derivatives. When used as a charge generation layer in a multilayer device, the composite material can enhance conductivity and charge generation and separation capabilities, thereby improving the performance of the light-emitting device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of display technology, and more specifically, to a composite material, a composite film, and their applications. Background Technology

[0002] Series-connected multilayer light-emitting devices connect at least two light-emitting layers in series through a charge generation layer. However, existing solution-based charge generation layers have poor charge generation and separation capabilities and low conductivity. Furthermore, inorganic N-type materials cannot be effectively matched with other organic functional materials, resulting in poor performance of solution-based multilayer light-emitting devices. Summary of the Invention

[0003] Based on this, the present application provides a composite material, a composite film, and their applications.

[0004] To address the aforementioned technical problems, this application provides a composite material, employing the technical solution described below:

[0005] A composite material comprising: an organic electron transport material and a dopant material, wherein the organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo-fluorene derivatives.

[0006] To address the aforementioned technical problems, this application also provides a composite film, employing the technical solution described below:

[0007] A composite thin film includes an n-type layer and a p-type layer stacked together, wherein the n-type layer comprises a composite material as described above, and the p-type layer comprises a hole transport material and a p-type doped material.

[0008] To address the aforementioned technical problems, this application also provides a light-emitting device, which employs the following technical solution:

[0009] A light-emitting device includes an anode and a cathode disposed opposite to each other, and at least two light-emitting layers stacked between the anode and the cathode; the light-emitting device further includes a charge-generating layer disposed between two adjacent light-emitting layers, wherein the charge-generating layer is a composite thin film as described above, the n-type layer is located on the side closer to the anode, and the p-type layer is located on the side closer to the cathode.

[0010] To address the aforementioned technical problems, this application also provides a display device that employs the following technical solution:

[0011] A display device includes the light-emitting device described above.

[0012] Compared with the prior art, the embodiments of this application have the following advantages: the organic electron transport material in the composite material can reduce the possibility of leakage, and the doped material in the composite material can improve the charge generation and separation capabilities, thereby improving the performance of the light-emitting device. Attached Figure Description

[0013] To more clearly illustrate the solution of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 This is a schematic diagram of the structure of one embodiment of a composite film in this application;

[0015] Figure 2 This is a schematic diagram of the structure of one embodiment of a light-emitting device in this application.

[0016] Figure reference numerals: 10, composite thin film; 11, n-type layer; 12, p-type layer; 20, anode; 30, cathode; 40, light-emitting layer; 50, hole-functional layer; 60, electron-functional layer. Detailed Implementation

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein in the specification of the application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application; the terms "comprising" and "having," and any variations thereof, in the specification, claims, and foregoing drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the specification, claims, or foregoing drawings of this application are used to distinguish different objects, not to describe a particular order.

[0018] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0019] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the orientation shown in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.

[0020] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0021] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c," or "at least one of a, b, and c," can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0022] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0023] In this application, "substitution" means that the hydrogen atom in the substituent is replaced by the substituent.

[0024] In this application, when no linking site is specified in the group, it means that any linkable site in the group is selected as the linking site.

[0025] In this application, when the same substituent appears multiple times, it can be independently selected from the same or different groups. If the general formula contains multiple R, then R can be independently selected from the same or different groups.

[0026] In this application, "ring atom number" refers to the number of atoms in the ring itself of a structural compound (e.g., a monocyclic compound, a fused-ring compound, a cross-linked compound, a carbocyclic compound, or a heterocyclic compound) obtained by atomic bonding to form a ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring-forming atoms. The same applies to the "ring atom number" described below unless otherwise specified. For example, a benzene ring has 6 ring atoms, a naphthalene ring has 10 ring atoms, and a thiophene group has 5 ring atoms.

[0027] In this application, "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing one hydrogen atom. It can be a monocyclic aryl, a fused-ring aryl, or a polycyclic aryl. For polycyclic rings, at least one is an aromatic ring system. For example, "substituted or unsubstituted aryl having 6 to 40 ring atoms" means an aryl containing 6 to 40 ring atoms, preferably a substituted or unsubstituted aryl having 6 to 30 ring atoms, more preferably a substituted or unsubstituted aryl having 6 to 18 ring atoms, particularly preferably a substituted or unsubstituted aryl having 6 to 14 ring atoms, and optionally further substituted on the aryl group; suitable examples include: phenyl, biphenyl, terphenyl, naphthyl, anthracene, phenanthrene, fluoranthracene, triphenylene, pyrene, perylene, tetraphenyl, fluorenyl, dinaphthylphenyl, acenaphthyl and their derivatives. Understandably, multiple aryl groups can also be interrupted by short non-aromatic units (e.g., <10% non-H atoms, such as C, N, or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, and diaryl ether systems should also be included in the definition of aryl.

[0028] In this application, "heteroaryl" refers to an aryl group in which at least one carbon atom is replaced by a non-carbon atom, which can be an N atom, an O atom, an S atom, etc. For example, "substituted or unsubstituted heteroaryl group having 5 to 40 ring atoms" refers to a heteroaryl group having 5 to 40 ring atoms, preferably a substituted or unsubstituted heteroaryl group having 6 to 30 ring atoms, more preferably a substituted or unsubstituted heteroaryl group having 6 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl group having 6 to 14 ring atoms. The heteroaryl group may optionally be further substituted, and suitable examples include: thiophene, furanyl, pyrrole, imidazolyl, triazolyl, imidazolyl, diazolyl, triazolyl, pyridyl, bipyridyl, pyrimidinyl, triazinyl, acridinel, pyridazinyl, pyrazinyl Quinolinyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridinylpyrimidinyl, pyridinylpyrazinyl, pyrazinylpyrazinyl, isoquinolinyl, indolyl, carbazoleyl, benzothiopheneyl, benzofuranyl, indolyl, carbazoleyl, pyrroloimidazolyl, pyrrolopyrrololyl, thienopyrrololyl, thienopyrrololyl, furanolololyl, furanolofuranyl, thienofuranyl, benzoisoxazolyl, benzoisothiazolyl, benzoimidazolyl, quinolinyl, isoquinolinyl, o-diazonyl, quinoxalinyl, phenanthridine, primidyl, quinazolinyl, quinazolinone, dibenzothiopheneyl, dibenzofuranyl, carbazoleyl and their derivatives.

[0029] In this application, "alkyl" can mean straight-chain, branched-chain, or cyclic alkyl. The number of carbon atoms in an alkyl group can be 1 to 50, 1 to 30, 1 to 20, 1 to 10, or 1 to 6. Phrases containing this term, such as "C1-9 alkyl," refer to alkyl groups containing 1 to 9 carbon atoms, and each time it appears, it can independently be C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, or C9 alkyl. Non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylpentyl, 3-methylpentyl, 2-ethylpentyl, 4-methyl-2-pentyl, n-hexyl, 1-methylhexyl, 2-ethylhexyl, 2-butylhexyl, n-heptyl, 1-methylheptyl, 2,2-dimethylheptyl, 2-ethylheptyl, 2-butylheptyl, n-octyl, tert-octyl, 2-ethyloctyl, 2-butyloctyl, 2-hexyloctyl, 3,7-dimethyloctyl, n-nonyl, n-decyl, adamantyl, 2-ethyldecyl, 2-butyldecyl, 2-hexyldecyl, 2-octyldecyl The compounds include: n-undecyl, n-dodecyl, 2-ethyldodecyl, 2-butyldodecyl, 2-hexyldodecyl, 2-octyldodecyl, n-tridecyl, n-tetradecyl, n-pentadecanyl, n-hexadecyl, 2-ethylhexadecyl, 2-butylhexadecyl, 2-hexylhexadecyl, 2-octylhexadecyl, n-heptadecyl, n-octadecyl, n-heptadecyl, n-eicosyl, 2-ethyleicosyl, 2-butyleicosyl, 2-hexyleicosyl, 2-octyleicosyl, n-monodecyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, n-eicosyl, and adamantane.

[0030] In this application, "alkoxy" refers to a group with the structure "-O-alkyl", that is, an alkyl group as defined above that is attached to other groups via an oxygen atom. Suitable examples of phrases containing this term include: methoxy (-O-CH3 or -OMe), ethoxy (-O-CH2CH3 or -OEt), and tert-butoxy (-OC(CH3)3 or -OtBu).

[0031] It should be noted that in this application, "substituted or unsubstituted" means that the defined group may or may not be substituted. When the defined group is substituted, it should be understood that the defined group can be substituted by one or more substituents R, wherein R can be selected from deuterium, cyano, isocyano, nitro, halogen, C1-C30 alkyl, heterocyclic group having 3-20 ring atoms, aryl group having 6-20 ring atoms, heteroaryl group having 5-20 ring atoms, -NR'R", silyl, carbonyl, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, haloformyl, formyl, isocyanate group, thiocyanate group, isothiocyanate group, hydroxyl, trifluoromethyl, and the above groups can also be further substituted by substituents acceptable in the art. In -NRaRb, Ra and Rb are each independently selected from hydrogen, deuterium, cyano, isocyano, nitro or halogen, C1-C10 alkyl, heterocyclic group having 3-20 ring atoms, aryl group having 6-20 ring atoms, and heteroaryl group having 5-20 ring atoms.

[0032] It should be noted that, in this application, the heteroatom in the heteroaryl group can be selected from one or more of O, S, and N.

[0033] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings.

[0034] Stacked light-emitting devices (LEDs) refer to LEDs that connect at least two light-emitting layers in series via a charge generation layer (CGL). Under the same product specifications, stacked LEDs offer a combination of superior brightness, efficiency, and lifetime compared to single-layer LEDs, making them a promising candidate for future products. Currently, in solution-based stacked LEDs, the n-type layer typically uses ZnO or its derivatives as the host material. While ZnO has strong electron injection capabilities, its coefficient of thermal expansion differs significantly from that of organic materials. Furthermore, each thin film in solution-based stacked LEDs requires thermal annealing, leading to variations in stress release. Specifically, during the thermal annealing process of stacked LEDs, where organic films are layered with ZnO films and then another organic film, ineffective stress release can cause film cracking. Moreover, the stacking of ZnO nanoparticles cannot achieve the same density as organic films, and the random arrangement of nanoparticles can lead to leakage current. These factors contribute to the poor performance of stacked LEDs. Moreover, currently, the doping materials in the n-type layer of the charge generation layer are usually alkali metals and their halides or metals, such as Li, Cs, and Yb, which effectively enhance electron injection; however, these materials cannot be solution-processed due to their high activity or metal composition.

[0035] To address the aforementioned issues, this application provides a composite material comprising: an organic electron transport material and a doped material, wherein the organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo-fluorene derivatives.

[0036] In this embodiment, when using composite materials to prepare the n-type layer, the organic electron transport material can be processed using a solution method. Furthermore, the difference in thermal expansion coefficient between the organic electron transport material and the film layers prepared from other organic materials in the light-emitting device is small, which can reduce the possibility of cracking in the n-type layer due to unreleased stress. Additionally, the n-type layer prepared using organic electron transport materials has excellent density, reducing the possibility of leakage. It should be noted that when preparing the n-type layer, in addition to considering the solubility and resistance to solvents of the organic electron transport material, its transport properties must also be considered. The organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo[3]fluorene derivatives. These derivatives possess a conjugated planar framework, and their electronic structure allows for charge transfer with other molecules, giving the organic electron transport material high transport properties. After mixing and reacting with dopant materials, they can effectively serve as the host material for existing n-type layers.

[0037] In this embodiment, the dopant material provides charge or hydrogen ions to the organic electron transport material. The dopant material that loses electrons forms a Coulomb pair with the organic electron transport material, and free charge carriers are released from the anion-cation pair. At the same time, they can exist stably in the film layer prepared using this composite material. The cation of the dopant material can achieve the n-type doping effect efficiently and stably. The film layer prepared by the composite material, as the n-type layer of the charge generation layer, can improve the charge generation and separation ability after contacting the p-type layer, thereby improving the performance of the light-emitting device.

[0038] Furthermore, the structural formula of the organic electron transport material is shown in Formula I, Formula II, or Formula III:

[0039]

[0040] R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 Each time it appears, it is independently selected from one or more combinations of H or D atoms, substituted or unsubstituted alkyl groups having 1 to 30 carbon atoms, substituted or unsubstituted alkoxy groups having 1 to 30 carbon atoms, substituted or unsubstituted cycloalkyl groups having 3 to 30 carbon atoms, substituted or unsubstituted aromatic groups having 6 to 60 cyclic atoms, or substituted or unsubstituted heteroaromatic groups having 5 to 60 cyclic atoms, NO2, N+R3, CF3, Cl, Br, F, CN, SO3H, CHO, COR, and COOH;

[0041] Adjacent R6, R7, and R8 can be connected to form a ring;

[0042] L1, L2, L3, and L4 are linking groups selected from one or more combinations of single bonds, double bonds, substituted or unsubstituted alkylene groups with 1 to 30 carbon atoms, substituted or unsubstituted alkenyl groups with 2 to 30 carbon atoms, substituted or unsubstituted alkynyl groups with 2 to 30 carbon atoms, substituted or unsubstituted etheryl groups with 2 to 30 carbon atoms, substituted or unsubstituted arylene groups, substituted or unsubstituted aryloxy groups, and substituted or unsubstituted arylthio groups.

[0043] In this embodiment, the organic electron transport material contains indene, fluorene, or indofluorene, which has a conjugated planar framework. Its electronic structure can transfer charge with other molecules, giving the organic electron transport material high transport performance. After being mixed and reacted with doped materials, it can effectively serve as the host material for existing n-type layers.

[0044] Furthermore, the structural formula of the doped material is shown in Formula IV:

[0045]

[0046] Formula IV;

[0047] Among them, R 13 R 14 Each time it appears, it is independently selected from one or more combinations of hydrogen atom, deuterium atom, cyano, isocyano, nitro, halogen, substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, substituted or unsubstituted aromatic group having 6 to 30 cyclic atoms, or substituted or unsubstituted heteroaromatic group having 5 to 30 cyclic atoms.

[0048] In this embodiment, the dopant material provides charge or hydrogen ions to the organic electron transport material. The dopant material that loses electrons forms a Coulomb pair with the organic electron transport material, and free charge carriers are released from the anion-cation pair. At the same time, they can exist stably in the film layer prepared using this composite material. The cations of the dopant material can achieve the n-type doping effect efficiently and stably. The film layer prepared by the composite material, as the n-type layer of the charge generation layer, can improve the charge generation and separation ability after contacting the p-type layer, thereby improving the performance of the light-emitting device.

[0049] Furthermore, the organic electron transport material is selected from at least one of the following structures:

[0050]

[0051]

[0052]

[0053] In this embodiment, the organic electron transport materials H1 to H14 have a conjugated structure. The conjugated structure allows electrons to move more freely in delocalized form within the molecule, forming a wide range of conjugated π bonds. When the molecule absorbs energy, electrons can jump from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Furthermore, due to the conjugated structure, electrons can more easily jump and transport between molecules, thereby improving electron transport performance.

[0054] In addition, the alkane chains on the side chains of organic electron transport materials H1 to H14 make them highly soluble, which is beneficial for preparing charge generation layers using solution methods.

[0055] In this embodiment, for details of the synthesis methods of organic electron transport materials H1 to H14, please refer to 10.1021 / ol8000574, 10.1002 / cphc.201601430, 10.1039 / C8QO00856F, 10.1021 / ja802266u, 10.1039 / C2JM14955A, 10.1039 / C0JM01173H, and 10.1039 / C8TC04313B.

[0056] Furthermore, the doped material is selected from at least one of the following structures:

[0057]

[0058] In this embodiment, dopants N1 to N6 provide charges or hydrogen ions to the organic electron transport material. The dopants that lose electrons form Coulomb pairs with the organic electron transport material, and free charge carriers are released from the anion-cation pairs. At the same time, they can all exist stably in the film layer prepared using this composite material. The cations of the dopants can achieve the n-type doping effect efficiently and stably. The film layer prepared by the composite material, as the n-type layer of the charge generation layer, can improve the charge generation and separation ability after contacting the p-type layer, thereby improving the performance of the light-emitting device.

[0059] In addition, compared with existing alkali metals and their halides or metal dopants, the doped materials N1 to N6 have better solubility, which is conducive to the preparation of charge generation layers by solution method.

[0060] For details on the synthesis methods of doped materials N1 to N6 in this embodiment, please refer to 10.1021 / acs.jpcb.2c05286, 10.1021 / acsami.2c05724, 10.1021 / acs.chemmater.9b01150, 10.1021 / ja403906d, 10.1002 / adma.201400668, and 10.1002 / aenm.201900817.

[0061] Furthermore, the mass ratio of the doped material to the organic electron transport material is (1-50):100.

[0062] In this embodiment, the mass ratio of the doped material to the organic electron transport material is (1-50):100, which enables the organic electron transport material to achieve n-type doping, thereby improving the electron injection capability.

[0063] Optionally, the mass ratio of the doped material to the organic electron transport material is (2-30):100.

[0064] In some optional embodiments of this example, the mass ratio of the doped material to the organic electron transport material is any one or any two of the following: 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, etc.

[0065] This application also provides a composite film 10, such as... Figure 1 As shown, the composite film 10 includes an n-type layer 11 and a p-type layer 12 stacked together. The n-type layer 11 includes the composite material described above, and the p-type layer 12 includes a hole transport material and a p-type doped material.

[0066] In this embodiment, when the n-type layer 11 is prepared using composite materials, the organic electron transport material can be processed using a solution method. Furthermore, the difference in thermal expansion coefficient between the organic electron transport material and the films prepared from other organic materials in the light-emitting device is small, which can reduce the possibility of cracking in the n-type layer 11 due to unreleased stress. Additionally, the n-type layer 11 prepared using organic electron transport materials exhibits excellent density, reducing the possibility of leakage. It should be noted that, in preparing the n-type layer 11, in addition to considering the solubility and resistance to solvents of the organic electron transport material, its transport properties must also be considered. The organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo[3]fluorene derivatives. These derivatives possess a conjugated planar framework, and their electronic structure allows for charge transfer with other molecules, giving the organic electron transport material high transport properties. After mixing and reacting with dopant materials, they can effectively serve as the host material for the existing n-type layer 11.

[0067] In this embodiment, the dopant material provides charge or hydrogen ions to the organic electron transport material. The dopant material that loses electrons will form a Coulomb pair with the organic electron transport material, and free charge carriers will be released from the anion-cation pair. At the same time, they can exist stably in the n-type layer 11. The cations of the dopant material can achieve the n-type doping effect efficiently and stably. The n-type layer 11 prepared by the composite material can improve the charge generation and separation ability after contacting the p-type layer 12, thereby improving the performance of the light-emitting device.

[0068] In this embodiment, the material of the p-type layer 12 includes hole transport material and p-type doped material, which can increase the hole carrier concentration of the p-type layer 12 and thus improve the hole transport capability.

[0069] Furthermore, the thickness of the n-type layer 11 is 1–50 nm.

[0070] In some optional embodiments of this example, the thickness of the n-type layer 11 is within the range of any one or any two of the following: 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc.

[0071] Furthermore, the thickness of the p-type layer 12 is 1–50 nm.

[0072] In some optional embodiments of this example, the thickness of the p-type layer 12 is within the range of any one or any two of the following: 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc.

[0073] Furthermore, the total thickness of the n-type layer 11 and the p-type layer 12 is 10–50 nm.

[0074] In some optional embodiments of this example, the total thickness of the n-type layer 11 and the p-type layer 12 is within the range of any one or any two of 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc.

[0075] In this embodiment, the composite thin film 10 is used as a charge generation layer. The total thickness of the n-type layer 11 and the p-type layer 12 is 10-50 nm, which can realize charge separation and adjust the voltage of the light-emitting device. The thickness of the n-type layer 11 and the p-type layer 12 can be allocated according to actual needs, and this application does not impose any restrictions on them.

[0076] Furthermore, the p-type doped material is selected from at least one of PEDOT:PSS, PEDOT:PSS-PFI, NDP-9, NDP-2, F4-TCNQ, F6-TCNNQ, HATCN, tetrafluorotetracyanoquinone dimethyl ether, 7,7,8,8-tetracyano-p-benzoquinone dimethyl ether, pentanebenzene, CuPc, WO3, MoO3, NiO, V2O5, CuO, WS2, and MoS2.

[0077] In this embodiment, the p-type doped material can increase the hole carrier concentration of the p-type layer 12, thereby improving the hole transport capability.

[0078] Further, the hole transport material is selected from 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4”-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)spiro, At least one of N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tris(N-carbazolyl)-triphenylamine, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, and N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine.

[0079] Furthermore, the mass ratio of the p-type doped material to the hole transport material is (1-50):100.

[0080] In this embodiment, the mass ratio of p-type doped material to hole transport material is (1-50):100, which enables the hole transport material to be p-type doped to improve hole transport capability.

[0081] Optionally, the mass ratio of the p-type doped material to the hole transport material is (1-10):100.

[0082] In some optional embodiments of this example, the mass ratio of the p-type doped material to the hole transport material is any one or any two of the following: 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, etc.

[0083] Specifically, when preparing the n-type layer 11, the organic electron transport material is dissolved in a first solvent to obtain a first solution, and the dopant material is dissolved in a second solvent to obtain a second solution. Then, according to the mass ratio of the dopant material to the organic electron transport material, the first solution and the second solution are thoroughly mixed to obtain a composite ink.

[0084] Specifically, the first solvent and the second solvent are each independently selected from at least one of common solvents such as toluene, chlorobenzene, xylene, carbon tetrachloride, diethyl ether, and anisole.

[0085] It should be noted that the required concentrations of the first and second solutions differ depending on the method used. For example, when using spin coating, for the same film thickness, a low-boiling-point (<150℃) low-concentration solution or a medium-boiling-point (150~250℃) high-concentration solution can be used. Therefore, it is sufficient to limit the mass ratio of the doped material to the organic electron transport material. The concentrations of the first and second solutions are determined according to actual needs, and this application does not impose any restrictions on them.

[0086] This application also provides a light-emitting device, such as... Figure 2 As shown, the light-emitting device includes an anode 20 and a cathode 30 disposed opposite to each other, and at least two light-emitting layers 40 stacked between the anode 20 and the cathode 30; the light-emitting device also includes a charge-generating layer disposed between two adjacent light-emitting layers 40, wherein the charge-generating layer is a composite thin film 10 as described above, the n-type layer 11 is located on the side closer to the anode 20, and the p-type layer 12 is located on the side closer to the cathode 30.

[0087] In this embodiment, when the n-type layer 11 of the composite film 10 is prepared using composite materials, the organic electron transport material can be processed by solution method. Furthermore, the difference in thermal expansion coefficient between the organic electron transport material and the film layer of the light-emitting layer 40 is small, which can reduce the possibility of cracking of the n-type layer 11 due to unreleased stress. Additionally, the n-type layer 11 prepared using the organic electron transport material has good density, reducing the possibility of leakage. It should be noted that when preparing the n-type layer 11, in addition to considering the solubility and resistance to solvents of the organic electron transport material, its transport properties also need to be considered. The organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo[3]fluorene derivatives. These derivatives have a conjugated planar framework, and their electronic structure allows for charge transfer with other molecules, giving the organic electron transport material high transport properties. After mixing and reacting with dopant materials, they can effectively serve as the main material for the existing n-type layer 11.

[0088] In this embodiment, the dopant material provides charge or hydrogen ions to the organic electron transport material. The dopant material that loses electrons will form a Coulomb pair with the organic electron transport material, and free charge carriers will be released from the anion-cation pair. At the same time, they can exist stably in the n-type layer 11. The cations of the dopant material can achieve the n-type doping effect efficiently and stably. The n-type layer 11 prepared by the composite material can improve the charge generation and separation ability after contacting the p-type layer 12, thereby improving the performance of the light-emitting device.

[0089] Furthermore, a hole-functional layer 50 is provided between the light-emitting layer 40 and the anode 20, and / or between the light-emitting layer 40 and the charge-generating layer.

[0090] Furthermore, an electronic functional layer 60 is provided between the light-emitting layer 40 and the cathode 30, and / or between the light-emitting layer 40 and the charge-generating layer.

[0091] Furthermore, the material of the light-emitting layer 40 includes at least one of organic light-emitting materials, perovskite nanoparticle materials, single-structure quantum dots, and core-shell structure quantum dots.

[0092] Furthermore, the organic light-emitting material is selected from at least one of F8BT, F8B2, PFO, PFO-DMP, PFB, PCz-C17, superyellow, MEH-PPV, MDMO-PPV, SY-PPV, PMMP, PVK:Ir(ppy)3, CBP:Ir(piq)3, and o-CBP:FIrPic.

[0093] Furthermore, the perovskite nanoparticle material is at least one of inorganic perovskite quantum dots, organic perovskite quantum dots, and organic-inorganic hybrid perovskite quantum dots, wherein the general structural formula of the inorganic perovskite quantum dots is AMX3, where A is Cs. + Ion, M is a divalent metal cation, M is selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2+ Yb 2+ and Eu 2+ One or more of the following, where X is a halide anion; and / or, the general structural formula of the organic perovskite quantum dot is CMX3, where C is formamidinyl; and / or, the general structural formula of the organic-inorganic hybrid perovskite quantum dot is BMX3, where B is selected from organic amine cations.

[0094] Furthermore, the materials of the single-structure quantum dots, the core material of the core-shell structure quantum dots, and the shell material of the core-shell structure quantum dots are each selected from at least one of group II-VI compounds, group IV-VI compounds, group III-V compounds, and group I-III-VI compounds. The group II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, and Hg. At least one of SeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe, wherein the IV-VI compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, Sn At least one of SeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, and A At least one of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, or InAlPSb, wherein the group I-III-VI compound is selected from at least one of CuInS2, CuInSe2, and AgInS2.

[0095] Further, the anode 20 and the cathode 30 are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode, and a composite electrode; wherein, the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene, and carbon fibers; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, ... The composite electrode material is selected from at least one of IZO, MZO, and AMO; the composite electrode material is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2; and / or

[0096] Further, the hole functional layer 50 includes a hole transport layer (not shown) and / or a hole injection layer (not shown). When the hole functional layer 50 includes a hole injection layer and a hole transport layer, the hole injection layer is disposed adjacent to the anode 20, and the hole transport layer is disposed adjacent to the cathode 30. The material of the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, T·APC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, polyaniline, titanium phthalocyanine, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene, and C60. The transition metal oxide is selected from NiO. x MoO x WO x CrO x or CuO x At least one of the following, wherein the transition metal sulfide compound is selected from MoS x MoSe x WS x 、WSe x or CuS xAt least one of the following: the hole transport layer material is selected from TFB, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS and its derivatives, TAPC, MCC, C60, 3-hexyl-substituted polythiophene, poly(N,N'-di(4-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine-CO-9,9-dioctylfluorene), 4,4',4”-tris(carbazole-9-yl)triphenylamine, 4,4'-di(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, doped or undoped graphene, NiO, MoO3, WO3, V2O5, CrO3, CuO or p-type gallium nitride.

[0097] Further, the electronic functional layer 60 includes an electron transport layer (not shown) and / or an electron injection layer (not shown). When the electronic functional layer 60 includes an electron injection layer and an electron transport layer, the electron injection layer is disposed adjacent to the cathode 30, and the electron transport layer is disposed adjacent to the anode 20. The material of the electron transport layer is selected from at least one of doped or undoped metal oxides and organic electron transport materials. The doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, zirconium oxide, barium oxide, aluminum oxide, tantalum oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, zinc lithium oxide, and indium tin oxide. The elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from methyl [6,6]-phenyl C71 butyrate, methyl [6,6]-phenyl C61 butyrate, organic fullerenes, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthrayl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazole-2-yl)benzene, 3,3'-[5'-[3-(3-pyridyl)phenyl], 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine, phenylpyridinium beryllium, 1,3,5-tris(1-phenyl-1H-benzimidazole-2-yl)benzene, 3 -(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole, 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene, tris-(8-hydroxyquinoline)aluminum, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10-phenanthroline, poly[(9,9-di(3'-((N,N-dimethyl)-N-ethylammonium)-propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)]dibromide, poly[(9,9-di(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)], 2,7-bis(diphenylphosphine oxide) -9,9'-spirobis[fluorene], 4,7-diphenyl-1,10-phenanthroline, lithium 8-hydroxyquinoline, bis(2-methyl-8-hydroxyquinoline-N1,O8)-(1,1'-biphenyl-4-hydroxy)aluminum, ion-conjugated polyelectrolyte, Alq3, TSPO1, TmPyPB, PBD, Beq2, TAZ, SPPO13; the material of the electron injection layer is selected from at least one of Yb, yttrium fluoride, Li, LiF, NaF, CeF, CsCO3, Cs, KBH4, lithium 8-hydroxyquinoline, bis(2-methyl-8-hydroxyquinoline-N1,O8)-(1,1'-biphenyl-4-hydroxy)aluminum, ion-conjugated polyelectrolyte or KH.

[0098] Specifically, there are two light-emitting layers 40 (hereinafter referred to as 40 and 40' for distinction) and hole functional layers 50 (hereinafter referred to as 50 and 50' for distinction). The light-emitting device includes a stacked anode 20, a first hole functional layer 50, a first light-emitting layer 40, a charge generation layer (i.e., composite thin film 10), a second hole functional layer 50', a second light-emitting layer 40', an electron functional layer 60, and a cathode 30. The first hole functional layer 50 includes a hole injection layer near the anode 20 and a hole transport layer near the first light-emitting layer 40. The second hole functional layer 50' includes a hole transport layer near the charge generation layer. The electron functional layer 60 includes an electron transport layer near the cathode 30.

[0099] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0100] Example 1:

[0101] Step 1: Preparation of composite ink: Obtaining the doped material and organic electron transport material in the composite material; wherein, the doped material is: Organic electron transport materials are:

[0102]

[0103] The dopant material was then dissolved in the second solvent (o-xylene) to obtain a second solution of 5 mg / mL; the organic electron transport material was then dissolved in the first solvent (o-xylene) to obtain a first solution of 20 mg / mL; the two first solutions and the second solution were then ultrasonically mixed at a volume ratio of 1:1 to obtain the composite ink; wherein the mass ratio of the dopant material to the organic electron transport material was 25:100.

[0104] Step 2: Provide a 50nm ITO anode substrate;

[0105] Step 3: PEDOT:PSS is solution deposited on the anode and annealed at 150°C for 20 min to obtain a hole injection layer with a thickness of 30 nm.

[0106] Step 4: Solution deposit TFB on the hole injection layer and anneal at 180°C for 20 min to obtain a hole transport layer with a thickness of 20 nm.

[0107] Step 5: Solution deposit F8BT on the hole transport layer and anneal at 140℃ for 20 min to obtain the first light-emitting layer with a thickness of 55 nm.

[0108] Step 6: Prepare the charge generation layer:

[0109] Step 6.1: Set the composite ink on the first light-emitting layer, then solution deposit the composite material, anneal at 150°C for 20 min, and obtain an n-type layer with a thickness of 30 nm;

[0110] Step 6.2: PVK:F4-TCNQ is deposited on the n-type layer by solution deposition and annealed at 150℃ for 20 min to obtain a p-type layer with a thickness of 20 nm; the n-type layer and the p-type layer are in contact to form a charge generation layer;

[0111] Step 7: Deposit F8BT on the p-type layer using solution method, anneal at 140℃ for 20 min, to obtain a second light-emitting layer with a thickness of 85 nm;

[0112] Step 8: Transfer the substrate to a vacuum chamber with a vacuum level of 9*10-7 torr, deposit NaF on the light-emitting layer to obtain an electron injection layer with a thickness of 1nm;

[0113] Step 9: Evaporate Al onto the electron injection layer to obtain a cathode with a thickness of 100 nm.

[0114] Example 2:

[0115] The difference from Example 1 is that the organic electron transport material is:

[0116]

[0117] Example 3:

[0118] The difference from Example 1 is that the organic electron transport material is:

[0119]

[0120] Example 4:

[0121] The difference from Example 1 is that the organic electron transport material is:

[0122]

[0123] Example 5:

[0124] The difference from Example 1 is that the organic electron transport material is:

[0125]

[0126] Example 6:

[0127] The difference from Example 2 is that the organic electron transport material is:

[0128]

[0129] Example 7:

[0130] The difference from Example 1 is that the organic electron transport material is:

[0131] Example 8:

[0132] The difference from Example 1 is that the organic electron transport material is:

[0133]

[0134] Example 9:

[0135] The difference from Example 2 is that the mass ratio of the doped material to the organic electron transport material is 1:100.

[0136] Example 10:

[0137] The difference from Example 1 is that the mass ratio of the doped material to the organic electron transport material is 50:100.

[0138] Example 11:

[0139] The difference from Example 1 is that the doped material is:

[0140] Example 12:

[0141] The difference from Example 1 is that the doped material is:

[0142] Example 13:

[0143] The difference from Example 1 is that the doped material is:

[0144] Comparative Example 1:

[0145] The difference from Example 1 is that there is no doped material; the composite material consists only of organic electron transport materials.

[0146] Comparative Example 2:

[0147] The difference from Example 1 is that step 4.1 involves solution deposition of ZnO on the light-emitting layer, followed by annealing at 100°C for 20 min to obtain an n-type layer with a thickness of 30 nm.

[0148] Comparative Example 3:

[0149] The difference from Example 1 is that steps 6 and 7 are omitted, and only the first light-emitting layer is present.

[0150] Comparative Example 4:

[0151] The difference from Example 1 is that the mass ratio of the doped material to the organic electron transport material is 75:100.

[0152] Test Result Analysis:

[0153] The current efficiency, driving voltage, and device lifetime of the light-emitting devices in Examples 1-13 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1.

[0154] The current efficiency test method is as follows: The current efficiency CE@1000nit uses the FPD optical property measurement equipment. The efficiency test system is built by controlling the QE PRO spectrometer, Keithley 2400 and Keithley 6485 through LabVIEW. The voltage, current, brightness and emission spectrum parameters are measured and the current efficiency is calculated.

[0155] The lifespan testing method is as follows: Under constant current density, the time required for each optoelectronic device to decay from its maximum brightness to 95% (T95h) is recorded. To shorten the testing cycle, device lifespan testing is usually performed at high brightness by accelerating device aging, and the lifespan at high brightness is obtained by fitting the extended exponential decay brightness decay fitting formula. For example, the lifespan at 1000 nits is measured as T95@1000nits. The specific calculation formula is as follows:

[0156]

[0157] Among them, T95 L T95's equivalent lifespan is 1000 nits. H For the measured lifetime at a certain constant current density, L H L represents the actual brightness of the device at a certain constant current density. L The lifetime is 1000 nits, and A is the acceleration factor. This experiment measured the lifetime of several groups of green OLED devices, where the constant current density was 25 mA / cm². 2 The value of A is 1.8.

[0158] Table 1

[0159]

[0160]

[0161] As shown in Table 1, the current efficiency and lifespan of Examples 1 to 13 are superior to those of Comparative Examples 1 and 2. The difference between Example 1 and Comparative Example 1 is that the n-type layer of Comparative Example 1 only includes organic electron transport materials, indicating that the doping material can stably achieve the n-type doping effect and improve charge generation and separation capabilities after contacting the p-type layer, thereby enhancing the performance of the light-emitting device. The difference between Example 1 and Comparative Example 2 is that the n-type layer of Comparative Example 1 uses ZnO, a material from the prior art, as the n-type layer material, indicating that using organic electron transport materials can reduce the possibility of leakage and has high transport properties. After mixing and reacting with the doping material, it can effectively serve as the main material of the existing n-type layer, thereby improving the performance of the light-emitting device.

[0162] Furthermore, Examples 2 to 13 changed the selection of organic electron transport material, the mass ratio of dopant material to organic electron transport material, and the selection of dopant material, respectively. However, the current efficiency and lifespan of Examples 2 to 13 were better than those of Comparative Examples 1 and 2, which further illustrates that the dopant material can stably achieve the n-type doping effect and can improve the charge generation and separation ability after contacting the p-type layer. In addition, the use of organic electron transport material can reduce the possibility of leakage current and has high transport performance. After mixing and reacting with the dopant material, it can effectively serve as the main material of the existing n-type layer, thereby improving the performance of the light-emitting device.

[0163] Furthermore, the difference between Comparative Example 3 and Examples 1 to 13 is that Comparative Example 3 has only one light-emitting layer. Therefore, the driving voltage of Comparative Example 3 is better than that of Examples 1 to 13. However, the current efficiency and lifespan of Examples 1 to 13 are better than those of Comparative Example 3, indicating that the current efficiency and lifespan of the stacked light-emitting device with two light-emitting layers are better than those of the light-emitting device with a single light-emitting layer.

[0164] Furthermore, the only difference between Comparative Example 4 and Example 1 is that the mass ratio of the doped material to the organic electron transport material is 75:100. However, the current efficiency and lifespan of Example 1 are better than those of Comparative Example 4, indicating that a mass ratio of the doped material to the organic electron transport material exceeding 50:100 will lead to oversaturation of the doped material. Excessive doped material may not react completely and may come into contact with other adjacent functional layers, thereby affecting the performance of the light-emitting device.

[0165] This application also provides a display device, which includes the light-emitting device described above.

[0166] In this embodiment, when using composite materials to prepare the n-type layer of the light-emitting device, the organic electron transport material can be processed using a solution method. Furthermore, the difference in thermal expansion coefficient between the organic electron transport material and the films prepared from other organic materials in the light-emitting device is small, which can reduce the possibility of cracking in the n-type layer due to unreleased stress. Additionally, the n-type layer prepared using organic electron transport materials has good density, reducing the possibility of leakage. It should be noted that when preparing the n-type layer, in addition to considering the solubility and resistance to solvents of the organic electron transport material, its transport properties must also be considered. The organic electron transport material is selected from one or more of indene derivatives, fluorene derivatives, and indo[3]fluorene derivatives. These derivatives possess a conjugated planar framework, and their electronic structure allows for charge transfer with other molecules, giving the organic electron transport material high transport properties. After mixing and reacting with dopant materials, they can effectively serve as the host material for existing n-type layers.

[0167] In this embodiment, the dopant material provides charge or hydrogen ions to the organic electron transport material. The dopant material that loses electrons forms a Coulomb pair with the organic electron transport material, and free charge carriers are released from the anion-cation pair. At the same time, they can exist stably in the n-type layer. The cations of the dopant material can achieve the n-type doping effect efficiently and stably. The n-type layer prepared by the composite material can improve the charge generation and separation ability after contacting the p-type layer, thereby improving the performance of the light-emitting device.

[0168] Obviously, the embodiments described above are only some embodiments of this application, not all embodiments. The accompanying drawings show preferred embodiments of this application, but do not limit the patent scope of this application. This application can be implemented in many different forms; rather, the purpose of providing these embodiments is to provide a more thorough and comprehensive understanding of the disclosure of this application. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing specific embodiments, or make equivalent substitutions for some of the technical features. Any equivalent structures made using the content of this application's specification and drawings, directly or indirectly applied to other related technical fields, are similarly within the scope of patent protection of this application.

Claims

1. A composite material, characterized in that, include: Organic electron transport materials and doped materials, wherein the organic electron transport materials are selected from one or more of indene derivatives, fluorene derivatives, and indo-fluorene derivatives.

2. The composite material according to claim 1, characterized in that, The structural formula of the organic electron transport material is shown in Formula I, Formula II, or Formula III: R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 Each time it appears, it is independently selected from one or more combinations of H or D atoms, substituted or unsubstituted alkyl groups having 1 to 30 carbon atoms, substituted or unsubstituted alkoxy groups having 1 to 30 carbon atoms, substituted or unsubstituted cycloalkyl groups having 3 to 30 carbon atoms, substituted or unsubstituted aromatic groups having 6 to 60 cyclic atoms, or substituted or unsubstituted heteroaromatic groups having 5 to 60 cyclic atoms, NO2, N+R3, CF3, Cl, Br, F, CN, SO3H, CHO, COR, and COOH; Adjacent R6, R7, and R8 can be connected to form a ring; L1, L2, L3, and L4 are linking groups selected from one or more combinations of single bonds, double bonds, substituted or unsubstituted alkylene groups with 1 to 30 carbon atoms, substituted or unsubstituted alkenyl groups with 2 to 30 carbon atoms, substituted or unsubstituted alkynyl groups with 2 to 30 carbon atoms, substituted or unsubstituted etheryl groups with 2 to 30 carbon atoms, substituted or unsubstituted arylene groups, substituted or unsubstituted aryloxy groups, and substituted or unsubstituted arylthio groups. And / or, the structure of the doped material is shown in Formula IV: Among them, R 13 R 14 Each time it appears, it is independently selected from one or more combinations of hydrogen atom, deuterium atom, cyano, isocyano, nitro, halogen, substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, substituted or unsubstituted aromatic group having 6 to 30 cyclic atoms, or substituted or unsubstituted heteroaromatic group having 5 to 30 cyclic atoms.

3. The composite material according to claim 2, characterized in that, The organic electron transport material is selected from at least one of the following structures:

4. The composite material according to claim 2, characterized in that, The doped material is selected from at least one of the following structures:

5. The composite material according to any one of claims 1 to 4, characterized in that, The mass ratio of the doped material to the organic electron transport material is (1-50):100; optionally, the mass ratio of the doped material to the organic electron transport material is (2-30):

100.

6. A composite film, characterized in that, It includes an n-type layer and a p-type layer stacked together, wherein the n-type layer comprises a composite material as described in any one of claims 1 to 5, and the p-type layer comprises a hole transport material and a p-type doped material.

7. The composite film according to claim 6, characterized in that, The p-type doped material is selected from at least one of PEDOT:PSS, PEDOT:PSS-PFI, NDP-9, NDP-2, F4-TCNQ, F6-TCNNQ, HATCN, tetrafluorotetracyanoquinone dimethyl ether, 7,7,8,8-tetracyano-p-benzodiquinone dimethyl ether, pentanebenzene, CuPc, WO3, MoO3, NiO, V2O5, CuO, WS2, and MoS2; and / or The hole transport material is selected from 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4”-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)spiro, N,N' At least one of the following: bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tris(N-carbazolyl)-triphenylamine, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine; and / or The mass ratio of the p-type doped material to the hole transport material is (1-50):100; optionally, the mass ratio of the p-type doped material to the hole transport material is (1-10):100; and / or The thickness of the n-type layer is 1–50 nm; and / or The thickness of the p-type layer is 1–50 nm; and / or The total thickness of the n-type layer and the p-type layer is 10–50 nm.

8. A light-emitting device, characterized in that, The light-emitting device includes an anode and a cathode arranged opposite to each other, and at least two light-emitting layers stacked between the anode and the cathode; the light-emitting device further includes a charge-generating layer disposed between two adjacent light-emitting layers, wherein the charge-generating layer is a composite film as described in any one of claims 6 to 7, the n-type layer is located on the side closer to the anode, and the p-type layer is located on the side closer to the cathode.

9. The light-emitting device according to claim 8, characterized in that, A hole-functional layer is provided between the light-emitting layer and the anode, and / or between the light-emitting layer and the charge-generating layer; and / or An electronic functional layer is provided between the light-emitting layer and the cathode, and / or between the light-emitting layer and the charge-generating layer; and / or The material of the light-emitting layer includes at least one of organic light-emitting materials, perovskite nanoparticles, single-structure quantum dots, and core-shell structure quantum dots; the organic light-emitting material is selected from at least one of F8BT, F8B2, PFO, PFO-DMP, PFB, PCz-C17, super yellow, MEH-PPV, MDMO-PPV, SY-PPV, PMMP, PVK:Ir(ppy)3, CBP:Ir(piq)3, and o-CBP:FIrPic; and / or, The perovskite nanoparticle material is at least one of inorganic perovskite quantum dots, organic perovskite quantum dots, and organic-inorganic hybrid perovskite quantum dots, wherein the general structural formula of the inorganic perovskite quantum dots is AMX3, where A is Cs. + Ion, M is a divalent metal cation, M is selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2+ Yb 2+ and Eu 2+ One or more of the following, where X is a halide anion; and / or, the general structural formula of the organic perovskite quantum dots is CMX3, where C is formamidinyl; and / or, the general structural formula of the organic-inorganic hybrid perovskite quantum dots is BMX3, where B is selected from organic amine cations; and / or The materials of the single-structure quantum dots, the core material of the core-shell structure quantum dots, and the shell material of the core-shell structure quantum dots are each selected from at least one of group II-VI compounds, group IV-VI compounds, group III-V compounds, and group I-III-VI compounds. The group II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, and HgSeTe. At least one of the following groups: HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe, wherein the group IV-VI compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, and SnSeT. e, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, Al At least one of PSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, or InAlPSb, wherein the group I-III-VI compound is selected from at least one of CuInS2, CuInSe2, and AgInS2.

10. The light-emitting device according to claim 9, characterized in that, The number of the light-emitting layer and the hole-functional layer is two, and the light-emitting device includes, in sequence, the anode, the first hole-functional layer, the first light-emitting layer, the charge-generating layer, the second hole-functional layer, the second light-emitting layer, the electron-functional layer, and the cathode; and / or The anode and the cathode are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode, and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene, and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2; and / or The hole functional layer includes a hole transport layer and / or a hole injection layer. When the hole functional layer includes a hole injection layer and a hole transport layer, the hole injection layer is disposed adjacent to the anode, and the hole transport layer is disposed adjacent to the cathode. The material of the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, T·APC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, polyaniline, titanium phthalocyanine, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene, and C60. The transition metal oxide is selected from NiO. x MoO x WO x CrO x or CuO x At least one of the following, wherein the transition metal sulfide compound is selected from MoS x MoSe x WS x 、WSe x or CuS x At least one of the following; the material of the hole transport layer is selected from TFB, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS and its derivatives, TAPC, MCC, C60, 3-hexyl-substituted polythiophene, poly(N,N'-di(4-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine-CO-9,9-dioctylfluorene), 4,4',4”-tris(carbazole-9-yl)triphenylamine, 4,4'-di(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, doped or undoped graphene, NiO, MoO3, WO3, V2O5, CrO3, CuO or p-type gallium nitride; and / or, The electronic functional layer includes an electron transport layer and / or an electron injection layer. When the electronic functional layer includes an electron injection layer and an electron transport layer, the electron injection layer is disposed adjacent to the cathode, and the electron transport layer is disposed adjacent to the anode. The material of the electron transport layer is selected from at least one of doped or undoped metal oxides and organic electron transport materials. The doped or undoped metal oxide is selected from at least one of doped or undoped zinc oxide, tin oxide, titanium oxide, zirconium oxide, barium oxide, aluminum oxide, tantalum oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, zinc lithium oxide, and indium tin oxide. The doped elements include aluminum, magnesium, lithium, manganese, yttrium, lanthanum, and copper. At least one of nickel, zirconium, cerium, and gadolinium; the organic electron transport material is selected from methyl [6,6]-phenyl C71 butyrate, methyl [6,6]-phenyl C61 butyrate, organic fullerenes, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthrayl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazole-2-yl)benzene, 3,3'-[5'-[3-(3-pyridyl)phenyl], 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine, phenylpyridinium beryllium, 1,3,5-tris(1-phenyl-1H-benzimidazole-2-yl)benzene, 3-(biphenyl-4-yl)-5- (4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole, 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene, tris-(8-hydroxyquinoline)aluminum, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, 4,7-diphenyl-1,10-phenanthroline, poly[(9,9-di(3'-((N,N-dimethyl)-N-ethylammonium)-propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)]dibromide, poly[(9,9-di(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-2,7-(9,9-dioctylfluorene)], 2,7-bis(diphenylphosphine oxide)-9,9'- The material of the electron injection layer is selected from at least one of spirobis[fluorene], 4,7-diphenyl-1,10-phenanthroline, lithium 8-hydroxyquinoline, bis(2-methyl-8-hydroxyquinoline-N1,O8)-(1,1'-biphenyl-4-hydroxy)aluminum, ion-conjugated polyelectrolyte, Alq3, TSPO1, TmPyPB, PBD, Beq2, TAZ, SPPO13; the material of the electron injection layer is selected from at least one of Yb, yttrium fluoride, Li, LiF, NaF, CeF, CsCO3, Cs, KBH4, lithium 8-hydroxyquinoline, bis(2-methyl-8-hydroxyquinoline-N1,O8)-(1,1'-biphenyl-4-hydroxy)aluminum, ion-conjugated polyelectrolyte or KH.

11. A display device, characterized in that, Includes the light-emitting device as described in any one of claims 8 to 10.